Aimery de Nabinaud, OFM (†1326), Counsellor of Henry II, Bishop of Paphos, Papal Diplomat between Cyprus and Armenia, and Debtor - Christopher Schabel (Perspektywy Kultury, 2023)
Of the four medieval cities (and dioceses) of Frankish Cyprus – Nicosia, Paphos, Limassol, and Famagusta – Paphos has received the least attention. Continuing work on the Bullarium Cyprium project, which involves editing the papal letters referring to the island, provides a window into the ecclesiastical history of the town. This is the second of three articles in this journal that complete Jean Richard’s work on the bishops of Paphos in the period of the Avignon papacy (1309–1377). With some notes on Bishop Jacques More (1309–1321), this paper focuses on his successor, Aimery de Nabinaud, OFM, the first member of an illustrious family of ecclesiastics who served Cyprus in the 14th century. First noted in 1310, when he was teaching at the Minorite convent in Famagusta, Aimery was an important advisor to King Henry II (†1324), he was eventually elevated to Bishop of Paphos in 1322. We know most about Aimery’s diplomatic activities with the Kingdom of Armenia in Cilicia from 1310 until his death, as well as the difficult financial situation he left to his successor as bishop, Géraud de Veyrines.